Efficacy and Cost of Molecular Identification of Clinical Mycobacterial Isolates in a Resource Limited Setting (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Many molecular methods of identification of mycobacteria are now available. With many molecular consumables now being available at low prices, routine identification in clinical laboratories is now possible, even in low/ middle income settings that have basic molecular facilities. This study was conducted to optimize a low cost PCR-RFLP based identification that can be used in such a laboratory.Methodology: DNA was extracted from mycobacterial cultures using five methods. Three were heat extraction and two were kit extraction methods. Yield and purity of extracted DNA was evaluated and PCR-RFLP was done on extracts to ensure that the DNA could be used for molecular assays. The method giving the highest yield at low cost was selected and DNA was extracted from 105 mycobacterial cultures from patients diagnosed with pulmonary tuberculosis. hsp65 PCR and restriction digestion with BstEII and HaeIII enzymes was done to identify mycobacteria, differentiate MTB complex from NTM and identify NTM species. gyrBPCR and restriction digestion with RsaI was done to identify MTB complex species. hsp65partial sequencing was done to confirm NTM species. Costs for molecular identification were calculated based on consumable cost.Results: Heat extraction in water (80 0C for 1 hour) provided a mean DNA yield of 30.07ng/μland mean A260/280 ratio of 1.45. Heat extraction methods gave significantly higher DNA yield compared to the kit extraction methods (ANOVA, p